Plasma assisted decontamination of biological and chemical agents - NATO Advanced Study Institute on Plasma Assisted Decontamination of Biological and Chemical Agents (2007 : Cesme, Turkey); Guceri, S. I. (Selcuk I.); Fridman, Alexander A., 1953-; Gibson, Katie; Haas, Christine; North Atlantic Treaty Organization. Public Diplomacy Division (Berlin : Springer, 2008)
Includes bibliographical references and index.